2013
DOI: 10.1002/mrm.24595
|View full text |Cite
|
Sign up to set email alerts
|

Lung morphometry using hyperpolarized 129Xe apparent diffusion coefficient anisotropy in chronic obstructive pulmonary disease

Abstract: Diffusion-weighted hyperpolarized (129) Xe MRI is a promising technique for mapping changes in human lung morphology and may be useful for early detection of emphysema associated with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(112 citation statements)
references
References 48 publications
7
101
4
Order By: Relevance
“…was confirmed in vivo by experimental measurements in humans , canines , mice , and rats using hyperpolarized 3 He gas. It was also recently confirmed in humans and rats using hyperpolarized 129 Xe gas. Example of the data obtained by Jacob et al from a rat for a broad range of b ‐values up to 40 s/cm 2 is shown in Figure where the authors compared fitting their data to the model in Eq.…”
Section: In Vivo Lung Morphometry Techniquementioning
confidence: 77%
See 1 more Smart Citation
“…was confirmed in vivo by experimental measurements in humans , canines , mice , and rats using hyperpolarized 3 He gas. It was also recently confirmed in humans and rats using hyperpolarized 129 Xe gas. Example of the data obtained by Jacob et al from a rat for a broad range of b ‐values up to 40 s/cm 2 is shown in Figure where the authors compared fitting their data to the model in Eq.…”
Section: In Vivo Lung Morphometry Techniquementioning
confidence: 77%
“…The first 129 Xe applications of in vivo lung morphometry technique have been demonstrated by Ruppert et al (see example in Fig. ) and Ouriadov et al in humans, and Boudreau et al , and Hegarty et al in rats.…”
Section: In Vivo Lung Morphometry Techniquementioning
confidence: 97%
“…The L m was calculated using Equation [12], and as shown in Equation [20], S/V was directly proportional to ADC. Finally, S/V 0 was generated using Equation [21] as follows:…”
Section: Stretched-exponential Modelmentioning
confidence: 99%
“…Importantly, estimates may also be generated for the mean linear intercept (L m ) and surface-to-volume ratio (S/V) (16), both welldescribed in the lung stereology literature (17). Previous work also established the relationship of lung MRI and histological measurements (16,(18)(19)(20), and evaluated emphysema patients (16,21), rodent models (18,20), lung cancer (22), and lung aging (23,24). In contrast, a singlecompartment model, as shown in Figure 1b, was also previously used to explain fluid diffusion in porous media (25) and to model 129 Xe (26), 19 F (27), and simulated inhaled-gas diffusion (28) in emphysematous tissue (29).…”
Section: Introductionmentioning
confidence: 99%
“…Because of these limitations, attention is turning to other gases such as 129Xe gas. [77][78][79][80] Although this agent is more abundant and less expensive, several technical challenges must be overcome before its role in the evaluation of emphysema can be properly understood. 80 Other potential agents include oxygen, Carbon-13 and perflouropropane.…”
Section: Mrimentioning
confidence: 99%